Transradial versus trans-femoral access site in high-speed rotational atherectomy in Sweden. (1st April 2022) - Desta, Liyew; Jurga, Juliane; Völz, Sebastian; Omerovic, Elmir; Ulvenstam, Anders; Zwackman, Sammy; Pagonis, Christos; Calle, Fredrik; Olivecrona, Göran K.; Persson, Jonas; Venetsanos, Dimitrios
Abstract: Background: Radial artery is the preferred access site in contemporary percutaneous coronary intervention (PCI). However, limited data exist regarding utilization pattern, safety, and long-term efficacy of transradial artery access (TRA) PCI in heavily calcified lesions using high-speed rotational atherectomy (HSRA). Methods: All patients who underwent HSRA-PCI in Sweden between 2005 and 2016 were included. Outcomes were major adverse cardiac events (MACE, including death, myocardial infarction (MI) or target vessel revascularisation (TVR)), in-hospital bleeding and restenosis. Inverse probability of treatment weighting was used to adjust for the non-randomized access site selection. Results: We included 1479 patients of whom 649 had TRA and 782 transfemoral artery access (TFA) HSRA-PCI. The rate of TRA increased significantly by 18% per year but remained lower in HSRA-PCI (60%) than in the overall PCI population (85%) in 2016. TRA was associated with comparable angiographic success but significantly lower risk for major (adjusted OR 0.16; 95% CI 0.05–0.47) or any in-hospital bleeding (adjusted OR 0.32; 95% CI 0.13–0.78). At one year, the adjusted risk for MACE (HR 0.87; 95% CI 0.67–1.13) and its individual components did not differ between TRA and TFA patients. The risk for restenosis did not significantly differ between TRA and TFA HSRA-PCI treated lesions (adjusted HR 0.92; 95% CI 0.46–1.81). Conclusion: HSRA-PCI by TRA was associated with significantly lower risk for in-hospital bleeding and equivalent long-term efficacy when compared with TFA. Our data support the feasibility and superior safety profile of TRA in HSRA-PCI. Highlights: In patients undergoing rotational atherectomy, the use of transradial access site has increased. Radial artery resulted in similar angiographic success with femoral artery. But radial artery was associated with significantly lower risk for bleeding. Radial artery was associated with similar long-term efficacy compared to femoral artery. Radial artery should be the preferable access site.